Tepid sponging plus dipyrone versus dipyrone alone for reducing body temperature in febrile children - Alves, João Guilherme Bezerra; Almeida, Natália Dornelas Câmara Marques de; Almeida, Camila Dornelas Câmara Marques de (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: The role of tepid sponging to promote fever control in children is controversial. We did not fi nd any studies reporting on the effectiveness of tepid sponging in addition to dipyrone. The aim of this study was to compare the effects of tepid sponging plus dipyrone with dipyrone alone for reducing fever. DESIGN AND SETTING: A randomized clinical trial was undertaken at Instituto Materno-Infantil Professor Fernando Figueira, Recife, Pernambuco. METHODS: Children from six months to fi ve years old with axillary temperature greater than 38 nC in the emergency ward between January and July 2006 were eligible. One hundred and twenty children were randomly assigned to receive oral dipyrone (20 mg/kg) or oral dipyrone and tepid sponging for 15 minutes. The primary outcome was mean temperature reduction after 15, 30, 60, 90 and 120 minutes. Secondary outcomes were crying and irritability. RESULTS: 106 children fi nished the study. After the fi rst 15 minutes, the fall in axillary temperature was signifi cantly greater in the sponged group than in the control group (p < 0.001). From 30 to 120 minutes, better fever control was observed in the control group. Crying and irritability were observed respectively in 52% and 36% of the sponged children and in none and only two of the controls. CONCLUSIONS: Tepid sponging plus dipyrone cooled faster during the fi rst 15 minutes, but dipyrone alone presented better fever control over the two-hour period. Tepid sponging caused mild discomfort, crying and irritability for most of the children.